Evaluasi User Experience Game Aaron Lost in the Jungle Menggunakan Metode Game Experience Questionnaire (GEQ) - Muhammad Iffaturrahman; Purnamasari, Dwi Amalia (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2025)
User experience is a crucial indicator in triggering the quality of interaction in digital games. This study aims to provide user experience in the game Aaron Lost in the Jungle using the Game Experience Questionnaire (GEQ) method. The GEQ instrument consists of four modules: the Core Module, the In-game Module, the Post-game Module, and the Social Presence Module. However, due to the single-player nature of the game, the Social Presence module was not implemented in this study. This study uses a quantitative descriptive approach, with data collection through a questionnaire and structured observations of 30 participants who have completed the game. Analysis was conducted on the mean and standard deviation of each experience dimension measured by each GEQ module. The analysis results show that the Tension/Annoyance dimension (3.250) and Negative Experience (2.961) obtained the highest scores, while Flow consistently showed the lowest scores across the two modules, namely 2.540 and 2.300. These findings indicate that although the game successfully elicits emotional engagement, there are still obstacles in building an optimal gaming experience. Several factors are thought to have contributed to this, including the lack of interactive tutorials, linear level design, and a lack of narrative elements. Therefore, further development focused on improving the instructional aspects and storyline is recommended to enhance the overall user experience.